HEADMASTER DECISION MODEL OF HUMAN RESOURCES DEVELOPMENT - Munib, Akhmad (The Journal of Educational Development, 2013)
Decision-making is an important thing at any time by a leader. In order decisions are taken in accordance with the objectives, the necessary information, values​​, and consultation with stakeholders. Head of Primary School of Pekunden and Islamic Al Azhar are  well-known figure in the area, because it is unique in taking decisions. Uniqueness of Pekunden Elementary School based values ​​attached to the school community that is associated with the timing, nature, and importance. While the head of the Islamic Primary School there is one thing that is different is the accountability to the foundation and to the Lord Almighty. To obtain the data used interview method is equipped with observation and documentation are carried out through a qualitative approach which aims to find the model, range, and impact of the principal decision-making in developing human resources in the State Primary School and Pekunden Islamic Al Azhar primary school Semarang. From the results of this study concluded that each school has a decision making model that is based on values​​, ways, and different approaches. As for advice to both (1) that the value that is owned by the school community not only is one thing to be considered in the decision, but it must be equipped with a reliable managerial skills, (2) should continue to explore, deepen, and expand their network in the school community to prepare a cadre of future leaders, and (3) seeks to minimize the impact of decision-making by increasing participation and communicate to the parties through a more humane approach.